The Pioneer Round of Translation: Features and Functions - Maquat, Lynne E. (2010)
In mammalian cells, newly synthesized mRNAs undergo a pioneer round of translation that is important for mRNA quality control. Following maturation of messenger ribonucleoprotein particles during and after the pioneer round, steady-state cycles of mRNA translation generate most of the cell’s proteins. Translation factors, RNA binding proteins and targets of signaling pathways that are particular to newly synthesized mRNAs regulate critical functions of the pioneer round.